Pharmacogenetic Aspects of the Interaction of AT1 Receptor Antagonists With ATP-Binding Cassette Transporter ABCG2 - Ripperger, Anne; Krischer, Anna; Robaa, Dina; Sippl, Wolfgang; Benndorf, Ralf A. (Frontiers in Pharmacology, 2018)
The ATP-binding cassette transporter ABCG2 (BCRP, MXR) is involved in the absorption, distribution, and elimination of numerous drugs. Thus, drugs that are able to reduce the activity of ABCG2, e.g. antihypertensive AT1 receptor antagonists (ARBs), may cause drug-drug interactions and compromise drug safety and efficacy. In addition, genetic variability within the ABCG2 gene may influence the ability of the transporter to interact with ARBs. Thus, the aim of this study was to characterize the ARB-ABCG2 interaction in the light of naturally occurring variations (F489L, R482G) or amino acid substitutions with in silico-predicted relevance for the ARB-ABCG2 interaction (Y469A; M483F; Y570A). For this purpose, ABCG2 variants were expressed in HEK293 cells and the impact of ARBs on ABCG2 activity was studied in vitro using the pheophorbide A (PhA) efflux assay. First, we demonstrated that both the F489L and the Y469A substitution, respectively, reduced ABCG2 protein levels in these cells. Moreover, both substitutions enhanced the inhibitory effect of candesartancilexetil, irbesartan, losartan, and telmisartan on ABCG2-mediated PhA efflux, whereas the R482G substitution blunted the inhibitory effect of candesartancilexetil and telmisartan in this regard. In contrast, the ARB-ABCG2 interaction was not altered in cells expressing either the M483F or the Y570A variant, respectively. In conclusion, our data indicate that the third transmembrane helix and adjacent regions of ABCG2 may be of major importance for the interaction of ARBs with the ABC transporter. Moreover, we conclude from our data that individuals carrying the F489L polymorphism may be at increased risk of developing ABCG2-related drug-drug interactions in multi-drug regimens involving ARBs.